PELAKSANAAN PENEGAKAN HUKUM PADA PERATURAN DAERAH DAERAH ISTIMEWA YOGYAKARTA NOMOR 1 TAHUN 2014 GUNA MENGATASI MASALAH PERGELANDANGAN DAN PENGEMISAN (STUDI KASUS NO. 24/PID.C/2021/PN SMN) - Haryati; Suryawan Raharjo; Eko Nurharyanto (Kajian Hukum, 2023)
The phenomenon of vagrancy and begging in the Special Region of Yogyakarta is a complex and ongoing social problem that negatively impacts public order and community quality of life. Despite efforts to address the issue through Regional Regulation No. 1/2014, the problem remains unresolved. Therefore, strategic criminal law enforcement and in-depth analysis are necessary. The method used to analyze the phenomenon or issue being studied is a normative legal research method, with primary data obtained from interviews, supplemented by secondary data from relevant legal documents, including the Penal Code (KUHP) and related regulations. Data collection techniques include interviews, documentation study, and analysis is conducted logically and juridically to draw conclusions. The implementation of the Minor Criminal Offenses (Tipiring) trial process for vagrancy and begging cases in Yogyakarta, as seen in Case No. 24/Pid.C/2021/PN Smn, demonstrates an efficient and streamlined judicial system. Regional Regulation No. 1/2014 serves as an effective legal basis for holistic handling through preventive, coercive, rehabilitative, and social reintegration approaches. Despite inter-institutional coordination and resource constraints, this policy has potential for creating inclusive and sustainable social order with active community participation.